Crime victims‘ right to compensation - Mrvić-Petrović Nataša (Temida, 2012)
This paper analyzes the most important documents of the United Nations, Council of Europe and the European Union relating to rights to damage compensation (restitution from offender and state compensation). The analysis shows that there is a gradual move from the concept of exercising the rights of victims in favor of a solidaristic model that takes less into account the rights of victims, and more the need to satisfy their legitimate interests. The economic crisis that is undermining the foundations of the welfare state could jeopardize the realization of this concept, especially in those European countries where the criminal justice system focuses solely on the offender, as is the case in Serbia. In such circumstances, regulation which protects the right to compensation, other rights and interests of victims, shall apply only to the extent that serves crime prevention. So it happens that in spite of a suitable normative framework and developments regarding the protection of victims of domestic violence and trafficking, the right to compensation and other rights of the victims do not actually get actualized in practice. In order to overcome this, a systemic reform to the criminal justice system should be undertaken with the aim to redirect the system towards the victim of the offense. Within these reforms a public fund for compensation of the victims of violence should be established and the process of mediation between the victim and the offender with the goal to make a settlement should be regulated, because these mechanisms do not exist in Serbia.